External Capital and Innovation Strategies Shaping Export Diversification in Developing Countries: An Empirical Exploration - Ramsha, Saleem (University of Malaysia Sarawak (UNIMAS), 2025)
The study investigates arguments regarding the impact of external resources and innovation strategies on export diversification along with finding the causality among export diversification, export growth, and economic development in developing countries. The sample is further divided into two sub-samples for in-depth inquiry. Generally, developing countries are not only striving to increase their exports but also remain engaged in diversifying them. An increase in export diversification requires funds to manage and maneuver the production scheme, to maintain a suitable and sustainable scenario. Developing countries suffer shortage of investment funds and lack the capacity to implement strategic plans in reaching the appropriate and productive outcome. Lack of capital potential in the domestic economy prompts a strong urge for external capital. The external capital is a unique strategy for external resources to meet with the investment challenges. Mostly, external resources take four forms which include foreign direct investment, remittances received, foreign aid, and external debt. Moreover, the strategic layout is captured through innovation strategies which include the technology choice index and patents filed by residents and non-residents in an economy. Hence, this study employed external capital resources and innovation strategies as crucial determinants of export diversification in the selected 65 developing countries for the period spanning from 1995 to 2021. Adopted estimation methods for this study are Cross-Sectional Auto Regressive Distributive Lag (CS-ARDL) model for mean outcome, whereby the effect of explanatory variables on quantiles of outcome variable is also estimated through Method of Moments Quantile Regression (MMQR). A few control variables are employed which include financial development, gross capital formation, market size, trade openness, and export growth. Three out of four external resources are significantly increasing export diversification in the employed sample. Innovation strategies are also significantly increasing export diversification. Keeping in view the importance of export diversification, export growth, and the market size of an economy, a causal relationship exists among them. Causality is estimated through the Panel Vector Auto Regression (PVAR) method. Bidirectional causality holds between export growth and economic growth for the sample countries. Growth-led diversification is also evident among them. Overall, the new trade theory is tested which has multifaceted dimensions for the sample panel. Developing countries should make a policy design for increasing external capital inflow and enhance innovation strategies to increase export diversification.